2003
DOI: 10.1074/jbc.m204652200
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the ERK Pathway by GTP-loaded Rap1 Requires the Concomitant Activation of Ras, Protein Kinase C, and Protein Kinase A in Neuronal Cells

Abstract: The small GTPases Ras or Rap1 were suggested to mediate the stimulatory effect of some G protein-coupled receptors on ERK activity in neuronal cells. Accordingly, we reported here that pituitary adenylate cyclase-activating polypeptide (PACAP), whose G protein-coupled receptor triggers neuronal differentiation of the PC12 cell line via ERK1/2 activation, transiently activated Ras and induced the sustained GTP loading of Rap1. Ras mediated peak stimulation of ERK by PACAP, whereas Rap1 was necessary for the sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 57 publications
5
80
0
Order By: Relevance
“…Furthermore, our findings suggested a role of Rap1 in the sustained phase of cAMP-induced ERK1/2 activation. This is in agreement with recent studies, which have shown that activation of Rap1 is required for the sustained phase of NGF-and PACAP-induced ERK1/2 activation (York et al, 1998;Bouschet et al, 2003). Thus, Rap1 might be essential for the sustained phase of ERK1/2 activation in response to a variety of different stimuli.…”
Section: )supporting
confidence: 81%
See 3 more Smart Citations
“…Furthermore, our findings suggested a role of Rap1 in the sustained phase of cAMP-induced ERK1/2 activation. This is in agreement with recent studies, which have shown that activation of Rap1 is required for the sustained phase of NGF-and PACAP-induced ERK1/2 activation (York et al, 1998;Bouschet et al, 2003). Thus, Rap1 might be essential for the sustained phase of ERK1/2 activation in response to a variety of different stimuli.…”
Section: )supporting
confidence: 81%
“…The band migrating above ERK1 is probably identical to ERK1b, a splice variant of ERK1 (Yung et al, 2000(Yung et al, ). al., 2001Enserink et al, 2002;Piiper et al, 2002;Norum et al, 2003;Bouschet et al, 2003).…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…These results identify two independent activities of the P2Y 2 receptor for enhancing neurotrophin-mediated differentiation: (i) increase in level of activated neurotrophin receptor and (ii) increased activation of ERK1͞2. In undifferentiated PC12 cells, P2Y 2 receptors increase intracellular calcium levels (56), which may activate PKC, Ras, and Raf, thereby activating ERK1͞2 (57). Activation of Raf by P2Y 2 receptors and TrkA could represent a convergence point for the two signaling pathways.…”
Section: Discussionmentioning
confidence: 99%